2012
DOI: 10.1007/s10900-012-9585-5
|View full text |Cite
|
Sign up to set email alerts
|

Resources, Roadblocks and Turning Points: A Qualitative Study of American Indian/ Alaska Native Adults with Type 2 Diabetes

Abstract: Type 2 diabetes is a worldwide health problem that has reached epidemic proportions in some communities. Alaska Native and American Indian (AN/AI) people are disproportionately diagnosed with type 2 diabetes and incidence is increasing in many Alaska communities. Developing effective interventions requires understanding the social and psychological factors that impact effective management of diabetes, yet little is known about these factors in AN/AI communities. The objective of this study was to explore perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…Sharing knowledge and experiences within a personal community can provide people with a sense of not being alone and offers a valued opportunity to exchange gain and reinforce existing knowledge relevant to a condition [21,22,42,43,45]. The process of sharing also feeds into people’s internal capacity to cope with stress and, though not always explicitly acknowledged, can act to motivate lifestyle changes or involvement by adding new activities with which to self-manage [21-23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharing knowledge and experiences within a personal community can provide people with a sense of not being alone and offers a valued opportunity to exchange gain and reinforce existing knowledge relevant to a condition [21,22,42,43,45]. The process of sharing also feeds into people’s internal capacity to cope with stress and, though not always explicitly acknowledged, can act to motivate lifestyle changes or involvement by adding new activities with which to self-manage [21-23].…”
Section: Resultsmentioning
confidence: 99%
“…Network influences can be both positive and negative [29,43]. However, overall in the literature there tends to be more positive network influences noted than negative ones, and more negative influences from family members than from friends [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Both techniques are well-accepted methods of qualitative research and have been used in studies regarding numerous disease states, including diabetes mellitus. [15][16][17][18][19][20] Interpretative phenomenology is an assessment technique used to gather qualitative data, 12 while thematic analysis is a technique used to analyze data obtained through qualitative research. [21][22][23] In thematic analysis, the researcher identifies patterns and themes in a subject's life and/or behavior, 14 which, in this study, consisted of a retrospective detailed investigation of participants' reflective writing about their active-learning diabetes simulation experience.…”
Section: Evauation and Assessmentmentioning
confidence: 99%
“…Native-American participants had cultural guilt from passing bad genes to descendants and also found the practice of hiding T2DM to from family and friends to avoid worrying others. Shaw et al (2013) found Native-Americans had the motivation to make lifestyle changes that were purposive, in order to live to see grandchildren age.…”
Section: Native-american Culturementioning
confidence: 99%